Real-World Application of Shankhaprakshalana (a Yogic Technique) in Bowel Preparation for Colonoscopy in a Busy Outpatient Clinic: An External Validation Study - Anirvan, Prajna; Nayak, Anil Kumar; Singh, Shivaram Prasad; Khatua, Chitta Ranjan; Panigrahi, Manas Kumar (Journal of Digestive Endoscopy, 2025)
Achieving optimal bowel preparation is pivotal for successful colonoscopy. However, in the real-world scenario, this is challenging. A recent study by Panigrahi et al sheds light on Shankhaprakshalana (SP) as a promising method in achieving optimal bowel preparation before colonoscopy. Our primary aim was to evaluate the effectiveness of SP in the bustling environment of a real-world outpatient clinic.It was a prospective study conducted at Kalinga Gastroenterology Foundation, Cuttack, between May and August 2024. Patients requiring colonoscopy underwent bowel preparation by SP using the previously described methodology. Patients having poor performance status, diagnosed with bowel stricture and with history of abdominal surgery, and those unable to perform SP were excluded. Bowel preparation was assessed using Boston Bowel Preparation Scale (BBPS).SP was performed in 101 patients. The mean age of the patients was 43.57 (±13.54) years. The mean BBPS score was 8.6 (±0.7). Bowel preparation was adequate in all patients (100%). The mean segmental BBPS for the three segments of the colon (right, transverse, and left) were 2.8 (±0.3), 3.0 (±0.6), and 3.0 (±0.6), respectively. Bowel preparation was completed in 143 (±24) minutes, with an average of 6 (±2) motions. The cecal intubation time was 7 (±3) minutes and the median visual analog scale (VAS) score for patient-reported discomfort during colonoscopy was 0 (0–5). Ninety-seven percent of the patients were willing to repeat the procedure using SP.In a busy, outpatient setting, SP is an efficacious and highly acceptable bowel preparation regimen prior to colonoscopy.
Keywords: bowel preparation solutions; bowel evacuants; effectiveness; acceptability; yoga